Peran Kebutuhan Akan Keunikan dan Pengaruh Teman Sebaya dalam Membentuk Sikap Konsumen Generasi Z terhadap Produk Bermerek di Samarinda - Arini Hudaya; Shafa Niswa Az-Zahra; Qanita Khairunnisa Darwis; Rania Fitra Bansir; Chandika Mahendra Widaryo; Lusiana Desy Ariswati (Indo Publishing, 2026)
This study aims to analyze the influence of need for uniqueness and peer influence on the attitudes of Generation Z consumers towards branded products in Samarinda. A quantitative approach with a survey method was employed, involving 100 respondents selected through purposive sampling with criteria: Generation Z (aged 18-27 years), residing in Samarinda, and having purchased or used branded products. Data were collected using a Likert scale questionnaire (1-5) and analyzed using SPSS, including validity test, reliability test, multiple linear regression, t-test, F-test, and coefficient of determination. The results showed that both need for uniqueness and peer influence partially and simultaneously have a positive and significant effect on the attitudes of Generation Z consumers towards branded products in Samarinda. The multiple linear regression equation obtained was ABP = 1.419 + 0.172(NFU) + 0.474(PI). The R Square value of 0.361 indicates that both independent variables are able to explain 36.1% of the variation in the dependent variable. Peer influence has a more dominant effect compared to need for uniqueness, as indicated by the standardized beta coefficient of 0.524. This finding confirms that social environment factors play a more important role than the need to stand out among Generation Z consumers in Samarinda. The results of this study are expected to contribute to the development of consumer behavior theory and become a reference for further research.